Time Prospects and Migratory Attitudes of Magadan Students at Different Stages of Education - Kuznetsova, S.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2018)
The relevance of the study is due to the insufficient knowledge of the influence of conditions the migration-mobile region on the formation of time perspectives for young people. The purpose was to study the correlation of time perspectives and migration attitudes of Magadan students at different stages of education. Methods: a questionnaire for studying the time perspectives of ZPTI F. Zimbardo in the adaptation of A. Syrtsova and the “Scale of Migratory Personality Attitudes”, based on the author’s concept of migration attitudes. Conclusions: the study showed that as learning in the university decreases the role of assessing the past in the territorial self-determination of Magadan students and the role of satisfaction/dissatisfaction with the present increases. The younger students, satisfied with the past, are more committed to the place of residence, and the students of the senior courses are satisfied with the present. The dual role of meaningful people in forming the time perspectives of the undergraduates is revealed: expectations from relatives and support for the student’s migratory attitudes open up a future time perspectives for him, and vice versa, the absence of such leads to frustration, a sense of hopelessness described in the terminology of ZPTI as a “fatalistic present”. The lack of a link between their own migration attitudes and the time perspectives of the future means that some of the purposeful students connect their perspectives with the actual place of residence, some with a possible move.